Stereotype validation the effects of activating negative stereotypes after intellectual performance. [article]. - Clark, Jason K.; Thiem, Kelsey C.; Barden, Jamie; Evans, Abigail T.
With regard to intellectual performance, a large body of research has shown that stigmatized group members may perform more poorly when negative, self-relevant stereotypes become activated prior to a task. However, no research to date has identified the potential ramifications of stereotype activation that happens after-rather than before-a person has finished performing. Six studies examined how postperformance stereotype salience may increase the certainty individuals have in evaluations of their own performance. In the current research, the accessibility of gender or racial stereotypes was manipulated after participants completed either a difficult math test (Studies 1-5) or a test of child-care knowledge (Study 6). Consistent with predictions, stereotype activation was found to increase the certainty that women (Studies 1,2,4, and 5), African Americans (Study 3), and men (Study 6) had toward negative evaluations of their performance. These effects emerged when performance-related perceptions were stereotype consistent rather than inconsistent (Studies 1-6) and were found to be most pronounced among those who were highly identified with the stereoptyped group (Study 5). Furthermore, greater certainty-triggered by negative stereotypes-predicted lowered domain-relevant beliefs (Studies 1,2,2, and 6) and differential exposure to domain-relevant stimuli (Studies 4 and 5). - - (from the authors)
Keywords: Certainty-Periodicals.; Metacognition-Periodicals.; Evaluation-Periodicals.; Stereotypes-Periodicals.; Test Performance-Periodicals.